Arachnid the king of spiders - Blade, Adam (Orchard Books, an imprint of Hachette Children's Group London, 2015)
In the caves of Avantia lurks Arachnid the King of Spiders. Arachnid preys on the local townspeople and guards a piece of the magical golden armour. Can Tom defeat the Beast and save the kingdom from destruction? -- back cover